Adenoid Cystic Carcinoma With Sialolithiasis of the Left Submandibular Gland: A Case Report and Literature Review. (May 2019) - Miyabe, Satoru; Ishibashi, Kenichiro; Saida, Kosuke; Fujiyoshi, Yukio; Fukano, Hideo; Ueda, Kaori; Ueda, Sei; Watanabe, Satoshi; Nagao, Toru
Adenoid cystic carcinoma is one of the most common salivary gland malignancies with poor long-term prognosis, but the coexistence of sialoliths is extraordinarily rare. In this article, we report a case of 30-year-old woman with a history of submandibular area swelling with intermittent pain increasing during mealtimes that had led her attending physician to diagnose a sialolith in the left submandibular gland on a radiograph 10 years before. However, the surgical specimen proved to be an adenoid cystic carcinoma accompanied with a sialolith. Histopathologically, the submandibular gland was displaced with a fibrous granulation tissue containing a small cribriform carcinoma invading the extracapsular region of the gland. We performed fluorescence in situ hybridization examination with an MYB-NFIB fusion probe of the lesion, with positive results. The patient underwent a supraomohyoid neck dissection as additional procedure because of the possibility of the extracapsular cancer nest remaining around the submandibular gland, but she remains well and disease free 11 years after the first operation.